Placental volume, vasculature and calcification in pregnancies complicated by pre-eclampsia and intra-uterine growth restriction. (December 2015) - Moran, Mary C.; Mulcahy, Cecelia; Zombori, Gergely; Ryan, John; Downey, Paul; McAuliffe, Fionnuala M.
Abstract: Objective: Pre-eclampsia (PET) and intrauterine growth restriction (IUGR), often associated with impaired placental function, are among the most common conditions contributing to increased perinatal mortality and morbidity. This study investigates if three dimensional power Doppler (3DPD) of the placenta and computerised analysis of placental calcification is different between PET/IUGR and normal pregnancies. Study design: This was a prospective cohort study involving 50 women with pre-eclampsia and/or IUGR, or with IUGR only from 24 to 40 weeks' gestation. 3DPD ultrasound was used to calculate placental volume, vascularisation index (VI), flow index (FI) and vascularisation-flow index (VFI). Following each scan the percentage of placental calcification was also calculated, by computer analysis. Results were compared with normal (control) values, and findings correlated with maternal and fetal Doppler parameters and placental histology. Results: Volume, VI, and VFI are not influenced by gestational age in PET/IUGR pregnancies. FI was found to increase with gestational age ( p  = 0.009) and was lower than normal in the total study group from 24 to 30 weeks ( p  = 0.006). In the pregnancies affected by PET, whether or not IUGR was present, all three indices were lower than normal values between 24 and 30 weeks (VI: p  = 0.038, FI: p  = 0.004, VFI: p  = 0.015). Vascularisation and flow indices were less than the normal 50th centile in the majority of cases of utero-placental insufficiency ( p  = 0.047), and vascularisation and vascularisation flow indices were lower in cases of accelerated placental maturation ( p  = 0.016 and 0.041 respectively). Placental volume greater than the 50th centile between 24 and 30 weeks was associated with the presence of infarction on histology ( p  = 0.021). Flow index ( p  = 0.002) and vascularisation flow index ( p  = 0.036) were lower in the presence of bilateral uterine artery notches. Calcification, similar to the control group, was related to an increasing UAPI ( p  = 0.041) and MCA PI <5th centile ( p  = 0.010). Conclusions: The study findings suggest that there may be a role for 3DPD placental assessment of volume, vascularisation and blood flow and computer analysis of placental calcification in the identification and management of PET/IUGR pregnancy.